Not All Women Are Mothers: Addressing the Invisibility of Women Under the Control of the Criminal Justice System Who Do Not Have Children - Michalsen, Venezia; Flavin, Jeanne (The Prison Journal, 2014)
Research has consistently shown that most women under the control of the criminal justice system are mothers. The robustness of this finding has been accompanied by a failure to consider the characteristics and needs of women without children. In this study, we examine data on 1,334 formerly incarcerated women. Findings indicate that while mothers and non-mothers share some characteristics, they differ on several others, most notably demographic profile, mental health, and timing of contacts with the criminal justice system. These results suggest a need to recognize the diversity among women offender groups, particularly when developing policies and programs need.
Keywords: dept.soc; peer-reviewed

More than Visiting Hours: Maintaining Ties Between Incarcerated Mothers and Their Children - Michalsen, Venezia; Flavin, Jeanne; Krupat, Tanya (Sociology Compass, 2010)
The majority of people in America’s prisons are the parents of minor children. Incarcerated mothers, in particular, were likely to have been a part of their children’s lives before their imprisonment, and most will soon be returning to the community and to their children. Research has shown that it is in the best interests of the mothers and the children to maintain a relationship across the prison bars. In this article, we use the example of New York State to show how institutional policies and structures can impede or encourage efforts to maintain ties between women and their children and why demonstrating support for family ties must extend well beyond having visiting hours.
Keywords: dept.soc; peer-reviewed

Abolitionist Feminism as Prisons Close: Fighting the Racist and Misogynist Surveillance “Child Welfare” System - Michalsen, Venezia (The Prison Journal, 2019)
The global prison industrial complex was built on Black and brown women’s bodies. This economy will not voluntarily loosen its hold on the bodies that feed it. White carceral feminists traditionally encourage State punishment, while anti-carceral, intersectional feminism recognizes that it empowers an ineffective and racist system. In fact, it is built on the criminalization of women’s survival strategies, creating a “victimization to prison pipeline.” But prisons are not the root of the problem; rather, they are a manifestation of the over-policing of Black women’s bodies, poverty, and motherhood. Such State surveillance will continue unless we disrupt these powerful systems both inside and outside prisons.
Keywords: dept.soc; peer-reviewed

Mothering and Desistance in Re-Entry - Michalsen, Venezia (Routledge, 2018)
Although there is plentiful research on the impact of marriage, employment and the military on desistance from criminal behaviour in the lives of men, far less
Keywords: dept.soc

A Cell of One’s Own? Incarceration and Other Turning Points in Women’s Journeys to Desistance - Michalsen, Venezia (International Journal of Offender Therapy and Comparative Criminology, 2019)
Research has shown the importance of turning points in desistance from criminal behavior. Using qualitative data from a sample of 100 formerly incarcerated mothers interviewed about their criminal behavior, this article explores their descriptions of transition moments and whether and how those moments affected their criminal behavior. The findings indicate that whereas parenting emerges as a turning point, the practical difficulties of reentry may reduce the impact of mothering on women’s desistance. More self-focused turning points, such as those due to incarceration, arrest, and sobriety appeared to be particularly important to the women’s desistance. This article emphasizes the need for research into the subjective and environmental factors that affect women’s desistance behaviors.
Keywords: dept.soc; peer-reviewed

Trigger Warnings: From Panic to Data - Laguardia, Francesca; Michalsen, Venezia; Rider-Milkovich, Holly (Journal of Legal Education, 2017)
Keywords: dept.soc; peer-reviewed

Mothering as a Life Course Transition: Do Women Go Straight for Their Children? - Michalsen, Venezia (Journal of Offender Rehabilitation, 2011)
In this study, qualitative, in-depth interviews were conducted with 100 formerly incarcerated mothers to explore the relationship between attachment to children and desistance from criminal behavior. Exploratory data analysis revealed that mothers do believe that children play important roles in their desistance, consistent with the tenets of life course theory. However, children were also described as sources of great stress, which may in turn promote criminal behavior. Women also related desistance to reliance on self and a higher power, and to a desire to avoid future involvement with the criminal justice system. The article concludes with a call for more research on women's desistance, and increased consideration of parent–child relationships in corrections policy decision making.
Keywords: attachment; children; dept.soc; desistance; life course theory; mothers; peer-reviewed; reentry

“I'm Not Good Enough for Anyone”: Legal Status and the Dating Lives of Undocumented Young Adults - Pila, Daniela (Sociological Forum, 2016)
The impact of legal status on romantic relationships has not been adequately explored in the literature. Based on video and phone interviews with 25 undocumented activists from the ages of 18 to 28 years old, this research examines how legal status affects the romantic relationships of undocumented women and men. The hegemony of traditional dating scripts made it difficult for those without legal status to participate. Gender roles were consistent with stereotypical male and female roles in dating, which often attribute more power and responsibility to men. As such, women experienced a slight advantage because traditional notions of courtship did not require them to provide the resources required for dating, such as money or transportation, which in contrast were commonly expected of the men. In contrast, women noted the difficulties of disclosing their legal status and depending on their partners for everyday activities. Additionally, both men and women faced exclusion that inhibited their dating lives, as a direct result of their legal status. This suggests that the impact of legal status may be salient at all stages of family formation and that undocumented young adults are experiencing a distinct phenomenon compared to their documented and native-born peers.
Keywords: citizenship; dating; dept.soc; immigration; legality; undocumented; young adults

Relocation as an Adaptation to Sea-Level Rise: Valuable Lessons from the Narikoso Village Relocation Project in Fiji. - Bertana, Amanda (Case Studies in the Environment, 2019)
Keywords: dept.soc

Curriculum Innovation Program Fellowship "Serving the Community Through Service Learning" - Jackson, Shirley A. (2011)
Dr. Jackson worked on her Curriculum Innovation Program fellowship, "Serving the community through service learning," completed write-up for Ethnic Studies Curriculum-Related Activity Grant for "Ethnic Studies Program Development at Southern Connecticut State University," worked on several articles and two book proposals encompassing research of race issues and their representation in contemporary cartoons, as well as attended conferences, both as a presenter and a chair, participated in workshops, and reviewed textbook chapters and an article.
Keywords: SCSU; Sabbatical leave report; dept.soc; faculty_collection; sabbatical_report

The Loveless Family: Getting Past Estrangement and Learning How to Love - Bloch, Jon P. (Praeger, 2011)
This scholarly and personal exploration of what it is like to grow up feeling unloved describes personality types and syndromes that often manifest, regardless of whether the family unit was "dysfunctional" or not., This scholarly and personal exploration of what it is like to grow up feeling unloved describes personality types and syndromes that often manifest, regardless of whether the family unit was ""dysfunctional"" or not.
Keywords: Families; Psychological aspects; Parenting; Dysfunctional families; Adult children of dysfunctional families; Love; dept.soc; faculty_collection

Ph.Dead - Bloch, Jon P. (Pegasus Books, 2016)
Keywords: College stories; dept.soc; faculty_collection

Identity Thief - Bloch, Jon P. (Bacon Press Books, 2014)
Keywords: Fiction; Identity theft; dept.soc; faculty_collection

Social Inequality and Social Stratification in US Society - Doob, Christopher Bates (Pearson, 2013)
Keywords: Equality; United States; United States; Social stratification; dept.soc; faculty_collection

Narcotic Addicts in Ukraine: Exploring Social Correlates of Addiction - Adams, Gregory A. (LAP Lambert, 2012)
Keywords: Drug addiction; Ukraine; dept.soc; faculty_collection

German Professionals in the United States a Gendered Analysis of the Migration Decision of Highly Skilled Families - Eich-Krohm, Astrid (New Americans (LFB Scholarly Publishing LLC), 2012)
Keywords: Emigration and immigration; Foreign workers, German; Germany; Immigrants; Germany; Professional employees; Social aspects; Social aspects; United States; Social conditions; Germany; United States; United States; Brain drain; United States; Professional employees; dept.soc; faculty_collection

Democracy Deferred: Civic Leadership After 9/11 - Woods, David W. (Palgrave Macmillan, 2012)
Keywords: 21st century; Civics; 21st century; September 11 Terrorist Attacks, 2001; History; Influence; Political participation; United States; dept.soc; faculty_collection

The Anatomy of Competition in Sports: The Struggle for Success in Major US Professional Leagues - Doob, Christopher Bates (Rowman & Littlefield, 2015)
Keywords: Professional sports; Psychology; Competition (Psychology); Success; United States; Athletes; dept.soc; faculty_collection

Great Expectations: The Sociology of Survival and Success in Organized Team Sports - Doob, Christopher B. (Routledge, 2018)
Keywords: dept.soc

Twenty-first-century trends in highly skilled migration - Eich-Krohm, A. (Routledge International Handbook of Migration Studies, 2013)
Keywords: dept.soc

Conclusion: Contemporary trends in the intersection of race, class, and gender - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Conversations on race, class, and gender - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Cultural contexts and identity - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Race, class, gender, and education - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Race, class, gender, and migration - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Race, class, gender, and sexualities - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Race, class, gender, and work - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

Routledge international handbook of race, class, and gender - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
The Routledge International Handbook of Race, Class, and Gender chronicles the development, growth, history, impact, and future direction of race, gender, and class studies from a multidisciplinary perspective. The research in this subfield has been wide-ranging, including works in sociology, gender studies, anthropology, political science, social policy, history, and public health. As a result, the interdisciplinary nature of race, gender, and class and its ability to reach a large audience has been part of its appeal. The Handbook provides clear and informative essays by experts from a variety of disciplines, addressing the diverse and broad-based impact of race, gender, and class studies. The Handbookis aimed at undergraduate and graduate students who are looking for a basic history, overview of key themes, and future directions for the study of the intersection of race, class, and gender. Scholars new to the area will also find the Handbook’s approach useful. The areas covered and the accompanying references will provide readers with extensive opportunities to engage in future research in the area. © 2015 Shirley A. Jackson.
Keywords: dept.soc

Theorizing race, class, and gender studies - Jackson, S.A. (Routledge International Handbook of Race, Class, and Gender, 2014)
Keywords: dept.soc

When enough is enough: African american women reclaiming themselves - Jackson, S.A. (Letting Go: Feminist and Social Justice Insight and Activism, 2015)
Keywords: dept.soc

Justice for the Poor: A Study of Criminal Defence Work - Emmelman, D.S. (Justice for the Poor: A Study of Criminal Defence Work, 2018)
This title was first published in 2003. In this study, the author examines the behavior of one group of court-appointed defence attorneys and reaches the conclusion that although, in contrast to popular opinion, these attorneys maintain an adversarial stance against the prosecutors and behave in a legally ethical (or "procedurally just") manner, case outcomes are unduly shaped by social class and are therefore substantively unjust. This occurs because poor defendants typically lack cultural rhetoric that favourably influences those who construct and operate the criminal court system. Ironically, this indicates that, in many cases, the process of plea bargaining may be more substantively just than trials. A major contribution of the study is the detailed analysis of the manner by which oppression and substantive injustice occur in the adjudication of many cases and how the cultural practices of the powerful can frequently misconstrue, exclude and mute the voices of the poor. © Debra S. Emmelman 2003.
Keywords: dept.soc

Belarus at the United Nations: An analysis of Belarus's global policy alignment following the Maidan revolution in Ukraine - Lennon, O.; Becker, A. (Demokratizatsiya, 2019)
Since the fall of the Soviet Union, Belarus has been the slowest of the countries in Eastern Europe to shake off its authoritarian past and ties with Russia. However, the Maidan revolution in Ukraine and Russia's subsequent annexation of Crimea and occupation of parts of Eastern Ukraine in 2014 might have forced Belarus's president, Aleksander Lukashenka, to start questioning the terms of this relationship. Russia's violation of Ukraine's sovereignty created a much more real possibility-and fear-that, if push came to shove, Russia would not hesitate to act similarly toward Belarus. Belarus's political choices are hard to predict: will it remain a dictatorship in Russia's shadow or will it embrace democracy and the rule of law and seek closer integration with the West? This study examines Belarus's global policy alignment from 2007 to 2017 by analyzing its voting patterns on contested issues-those on which Russia's and the U.S.'s votes diverged-at the United Nations General Assembly. While Belarus seems to have been disassociating itself from Russia on some global issues, as evidenced by its voting record at the UN General Assembly, and its democracy level increased from 2014-2016, there is insufficient evidence to believe that Belarus might in fact be aligning more with the West and moving away from Russia. While Belarus's diplomatic pendulum has increasingly swung toward the US, it has inevitably bounced back to its "home base"-Russia. © 2019 Heldref Publications. All rights reserved.
Keywords: Belarus; Crimea; Russian Federation; Ukraine; United Nations; authoritarianism; democracy; dept.soc; diplomatic relations; international relations; peer-reviewed; policy approach; sovereignty; voting behavior; ⛔ No DOI found

Connecticut - Kenty-Drane, Jessica L.; Prince-Stewart, Jamilah (Sociology of Education: An A-to-Z Guide, 2013)
The sociology of education is a rich interdisciplinary field that studies schools as their own social world as well as their place within the larger society. The field draws contributions from education, sociology, human development, family studies, economics, politics and public policy. Sociology of Education: An A-to-Z Guide introduces students to the social constructions of our educational systems and their many players, including students and their peers, teachers, parents, the broader community, politicians and policy makers. The roles of schools, the social processes governing schooling, and impacts on society are all critically explored. Despite an abundance of textbooks and specialized monographs, there are few up-to-date reference works in this area. Features & Benefits: 335 signed entries fill 2 volumes in print and electronic formats, providing the most comprehensive reference resource available on this topic. Cross-References and Suggestions for Further Reading guide readers to additional resources. A thematic "Reader's Guide" groups related articles by broad topic areas as one handy search feature on the e-Reference platform, which also includes a comprehensive index of search terms, facilitating ease of use by both on-campus students and distance learners. A Chronology provides students with historical perspective on the sociology of education.
Keywords: dept.soc

Wealth and education - Kenty-Drane, Jessica L. (Sociology of Education: An A-to-Z Guide, 2013)
The sociology of education is a rich interdisciplinary field that studies schools as their own social world as well as their place within the larger society. The field draws contributions from education, sociology, human development, family studies, economics, politics and public policy. Sociology of Education: An A-to-Z Guide introduces students to the social constructions of our educational systems and their many players, including students and their peers, teachers, parents, the broader community, politicians and policy makers. The roles of schools, the social processes governing schooling, and impacts on society are all critically explored. Despite an abundance of textbooks and specialized monographs, there are few up-to-date reference works in this area. Features & Benefits: 335 signed entries fill 2 volumes in print and electronic formats, providing the most comprehensive reference resource available on this topic. Cross-References and Suggestions for Further Reading guide readers to additional resources. A thematic "Reader's Guide" groups related articles by broad topic areas as one handy search feature on the e-Reference platform, which also includes a comprehensive index of search terms, facilitating ease of use by both on-campus students and distance learners. A Chronology provides students with historical perspective on the sociology of education.
Keywords: dept.soc

Book Review: Black Woman’s Burden: Commodifying Black Reproduction - Jackson, Shirley A. (Contemporary Sociology, 2010)
Keywords: book.review; dept.soc

Backlash 9/11: middle eastern and muslim americans respond - Woods, David W. (Mobilization, 2011)
Keywords: dept.soc; ⛔ No DOI found

Book Review: women: judith schoenen, das image der frau — wege zu einem neuen selbstbild [A woman’s image — path to a new Self-Portrait]. opladen and farmington hills, MI: barbara budrich, 2008, 172 pp., ISBN 9783866491007, 12.90 - Eich-Krohm, Astrid (International Sociology, 2010)
Keywords: book.review; dept.soc

The CDU and the politics of gender in germany: bringing women to the party - Eich-Krohm, Astrid (Gender & Society, 2012)
Keywords: dept.soc

Is Fifty Really the New Thirty? The Stigma of Age as a Form of Strain and its Role in Drug and Alcohol Abuse and Dependence by Women - Black, Pamela; Brown, Alan D. (Deviant Behavior, 2016)
Aging bodies stigmatize women. The effects of stigma, health issues, goal disappointment, and a combination of age and minority group status, overwhelm older women's coping strategies, leading to maladaptive behaviors. General strain theory posits a relationship between negative stimuli and deviant behavior. Advancing age and age-related stigma reflect this strain. This study explores the relationship between strain and substance abuse or dependence, comparing subsamples of middle age (35- to 49-year-old women) and older middle age (50- to 64-year-old) women. Data suggest that minority age status coupled with acute or mental health issues increase substance abuse or dependence by older women.
Keywords: dept.soc

Organizing lesbian/queer bathhouse events: Emerging forms of sexual experience. - Brown, A D; Gailey, Nerissa (Journal of Lesbian Studies, 2016)
Discussions of public sexual spaces in the social science literature have, until recently, been dominated by analyses of men's use of these spaces for erotic expression. In the late 1990s, feminist collectives began to explore the emancipatory potentials these spaces can have for lesbian sexualities. After a police raid on one such event called the "Pussy Palace," scholars in diverse disciplines began to explore how these events have both opened up and restricted erotic possibilities for lesbians, queer women, and trans* attendees. This article reviews the existing social science literature on lesbian and queer bathhouse events and highlights several key themes and subthemes that have dominated the discourse, including the importance that these spaces be recognized for their ability to both shape and be shaped by principles of community, safety, and sexual health/wellness.
Keywords: *Homosexuality, Female; *Homosexuality, Male; *Public Facilities; *Sexual Behavior; Baths; Female; Homosexuality, Female; Homosexuality, Male; Humans; Lesbian; Male; Public Facilities; Sexual Behavior; Social Behavior; bath; bathhouse; dept.soc; ethic of care; female; human; lesbianism; male; male homosexuality; public sex; sanitation; sexual behavior; sexual politics; social behavior

Beyond either/or: Reading trans* lesbian identities. - Gailey, Nerissa; Brown, A D (Journal of Lesbian Studies, 2016)
Previous research has explored the affiliation and distancing strategies employed in published memoirs of gender transition. In this article, we are particularly interested in elucidating the ways in which individuals construct identities and characterize their sexualities, and how sociohistorical constraints might influence what is expressed with respect to this in personal narratives of transition. Using the memoirs of Lili Elbe (Hoyer, 1933) and Joy Ladin (2013) as conceptual brackets, this article investigates the complex relationship between the development and articulation of trans* identities and lesbian sexualities within the context of published memoirs of gender transition.
Keywords: *Homosexuality, Female/px [Psychology]; *Transgender Persons/px [Psychology]; Female; Gender Identity; Homosexuality, Female; Humans; Lesbian; Male; Personal Narratives as Topic; Sex Reassignment Surgery; Sex Reassignment Surgery/px [Psychology]; Transgender Persons; Women's Rights; dept.soc; female; feminist movements; gender identity; human; identity; lesbianism; literature; male; memoirs; psychology; sex reassignment; sexuality; trans*; transgender; women's rights

“A grain of salt in a pepper shaker”: interviewing whites, blacks, and latinos about their neighborhood preferences - Meyerhoffer, Cassi A (Sociological Forum, 2016)
Several perspectives dominate as explanations for neighborhood preferences: pure race, racial proxy, race-based neighborhood stereotyping, and race-associated neighborhood factors. This analysis extends and supports the pure race and race-associated neighborhood factors arguments by showing that these theories are applied differently depending on respondents' social class, race and ethnicity, and whether they are talking about white, black, or Latino neighborhoods. Race-associated factors are emphasized for white and black neighborhoods, but pure race serves as a better theoretical framework for understanding people's preferences for Latino neighborhoods. I analyze qualitative interview data, using maps of real neighborhoods and hypothetical neighborhood show cards, to examine the neighborhood preferences of 65 white, black, and Latino residents in Ogden, Utah, and Buffalo, New York.
Keywords: African Americans; Latinos; dept.soc; neighborhood racial association; pure race; racial proxy; racial residential segregation

"I have more in common with Americans than I do with illegal aliens" culture, perceived threat, and neighborhood preferences - Meyerhoffer, Cassi A (The Sociology of Race and Ethnicity, 2015)
Keywords: dept.soc

Book Review: social order and the fear of crime in contemporary times, by stephen farrall, jonathan jackson, and emily gray. new york, NY: oxford university press, 2009. 319pp. 100.00 cloth. ISBN: 9780199540815 - Adams, Gregory (Contemporary Sociology, 2011)
Keywords: book.review; dept.soc; ⛔ No DOI found

Social order and the fear of crime in contemporary times - Adams, Gregory (Contemporary Sociology-a Journal of Reviews, 2011)
Keywords: dept.soc

Principles of racial integration vs. perceptions of non-White neighborhoods: Comparing hypothetical and real neighborhood choice - Meyerhoffer, Cassi A.; Kenty-Drane, Jessica (Journal of Urban Affairs, 2019)
Using qualitative interview data, we examine the consistency of White residents' responses to questions about their preferences for the racial composition of their neighborhoods when comparing hypothetical showcards and maps of real neighborhoods in respondents' cities. This approach allows for an examination of how residents' preferences for real neighborhoods align with preferences for idealized neighborhoods and the explanations people give when describing their preferences for neighborhoods of color. Data come from qualitative interviews conducted in Buffalo, New York, and Ogden, Utah.
Keywords: Buffalo; New York [New York (STT)]; New York [United States]; Ogden; United States; Utah; data set; dept.soc; neighborhood; peer-reviewed; perception; qualitative analysis; racial disparity; racial segregation

All is quiet on the Russian front: ceasefires and the pursuit of legitimacy by self-proclaimed “republics” in Ukraine - Lennon, Olena; Adams, Gregory (Eurasian Geography and Economics, 2019)
This paper examines the pursuit of legitimacy by the self-proclaimed “republics” in Ukraine. While these “republics” are illegal, questions of their legitimacy are commonly discussed almost entirely through Weberian rule-conformity. We argue that this one-dimensional view of legitimacy overlooks the rich context of normative aspects of power relationships. If the occupied Donbas is to be reintegrated into Ukraine, it is essential to understand the perceived legitimation of the political institutions in this region. We use David Beetham’s framework of legitimacy—consisting of legality, morality, and consent—to analyze the “republics’” pursuit of legitimacy. Our analysis leads to the proposition that while the “republics” are illegal, their supporters’ normative perceptions of the right to govern have ascribed more validity to the fake “governments” than what would have been expected from a legal point of view. Additionally, while a ceasefire between the Russian proxies and Ukraine’s forces has reduced violence, it has also levied temporal effect on the legitimation of illegitimate institutions. Our treatment of the process of legitimation over time helps us identify potential strategies of delegitimization should DPR and LPR reincorporate with Ukraine-controlled territory. Without dismantling internal perceptions of institutional legitimacy among inhabitants of nongovernment-controlled areas, a re-integration could not be accomplished.
Keywords: Russia; Ukraine; conflict management; de facto states; dept.soc; institutional framework; legislation; legitimacy; peer-reviewed; political conflict; political power; reconciliation; secessionism; separatism

Understanding the potential of state-based public health genomics programs to mitigate disparities in access to clinical genetic services - Senier, Laura; Tan, Catherine; Smollin, Leandra; Lee, Rachael (Genetics in Medicine, 2019)
Keywords: dept.soc; peer-reviewed

The yoke of childhood - Misgivings about children's relationship to technology in contemporary science fiction - Kenty-Drane, Jessica L. (Child and youth agency in science fiction: travel, technology, time, 2019)
Keywords: dept.soc; faculty_collection

A life-course perspective on incarcerated women’s views on adulthood - Umamaheswar, Janani (Women & Criminal Justice, 2018)
Keywords: dept.soc; peer-reviewed

Studying homeless and incarcerated persons: A comparative account of doing field research with hard-to-reach populations - Umamaheswar, Janani (Forum Qualitative Sozialforschung, 2018)
In this article, I discuss the process of conducting research with two vulnerable and hard-to-reach populations (homeless and incarcerated men) in three research locations characterized by varying levels of gatekeeping: a prison, public streets in an urban city, and a residential facility for homeless men. I argue that, despite the obstacles to independent research that gatekeepers (officials who can grant or deny researchers access to participants) pose, research with vulnerable, hard-to-reach populations in different field sites reveals some of the benefits of using field sites characterized by gatekeeping and strict rules to which researchers must adhere. Many of these benefits, however, go unacknowledged in discussions of access in qualitative studies—especially in the penological literature. I conclude that, instead of shying away from qualitative prison studies, researchers should take advantage of the benefits that prisons offer as field sites.
Keywords: Access; Feldforschung; Field research; Gatekeeping; Gefängnis; Gefängnisforschung; Grounded theory methodology; Grounded-Theory-Methodologie; Homelessness; Interviewing; Interviews; Obdachlosigkeit; Prison; Prison research; Zugang; access; dept.soc; field research; gatekeeping; grounded theory methodology; homelessness; interviewing; peer-reviewed; prison; prison research

Book Review: 'Connecting in college: How friendship networks matter for academic and social success' by J. M. McCabe - Kenty-Drane, Jessica L. (American Journal of Sociology, 2018)
Keywords: book.review; dept.soc; peer-reviewed

Navigating the evidentiary turn in public health: Sensemaking strategies to integrate genomics into state-level chronic disease prevention programs - Senier, Laura; Smollin, Leandra; Lee, Rachael; Nicoll, Lauren; Shields, Michael; Tan, Catherine (Social Science & Medicine, 2018)
Keywords: dept.soc; peer-reviewed

“I'm a normal autistic person, not an abnormal neurotypical”: Autism Spectrum Disorder diagnosis as biographical illumination - Tan, Catherine D. (Social Science & Medicine, 2018)
Keywords: dept.soc; peer-reviewed